Transforming Out-of-School Education: The Role of Teacher Digital Literacy in Enhancing Learning Quality - Yuni Rohimatus Syamsiyah; Abu Hasan Agus R; Qisthi Efridita (Universitas Nurul Jadid, 2026)
This study aims to investigate the role of teacher digital literacy in enhancing learning quality in primary schools, particularly in contexts with limited access to technology. Education in remote areas faces persistent structural challenges, including limited digital devices, unstable internet connectivity, and varying teacher readiness. Teacher digital literacy, encompassing the ability to select, adapt, and integrate technology into pedagogical practices, is critical for fostering inclusive and effective learning. A qualitative case study approach was employed, involving observations, interviews, desk reviews, and interview guides to capture teachers’ experiences, strategies, and challenges in implementing digital literacy. Findings indicate that digitally literate teachers enhance learning processes through platforms such as Google Classroom and Zoom, strengthen communication and collaboration with students, and leverage objective evaluation data to design adaptive instructional strategies. Additionally, the use of digital learning resources fosters student motivation, autonomy, and engagement. The study recommends teacher professional development programs that emphasize the integration of pedagogy and technology, alongside infrastructure improvements to support sustainable educational transformation.